Frequency of neovascular lesion types in wet age-related macular degeneration - Gierek-Łapińska, Ariadna; Wykrota, Halina; Trzciąkowski, Krzysztof; Szymkowiak, Monika; Gierek-Ciaciura, Stanisława (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
Age-related macular degeneration (AMD) is the most common cause of legal blindness among the urbanized world. Neovascular type of the disease which is responsible for majority of severe vision loss in course of AMD has received few years ago a new treatment modality – photodynamic therapy (PDT) with verteporfin (Visudyne). Efficacy of PDT depends on angiographic feature of chorioneovascularization (CNV). There are three main types of CNV: predominantly classic, minimally classic and occult with no classic CNV. No population studies on prevalence of these types are available. We analyzed fluorescein angiography (FA) performed in Eye Clinic of Silesian School of Medicine in Katowice, Poland. FA were performed between January 2002 and March 2004. 2942 cases of CNV due to AMD was identified and their type was stated. Statistical assessment of CNV types frequency was executed. CNV location and size was defined as well. Visual acuity data from patients medical history was used for deeper analysis.